ANALISIS KINERJA PEGAWAI DI SANGGAR KEGIATAN BELAJAR (SKB) JLN. KHATIB SULTAN NO. 3 KELURAHAN KEMBANG KENANGA KEC. SAIL KOTA PEKANBARU - Fernando, Alex; Sumardi, Sumardi; Jas, Jaspar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research was conducted at the Learning Activity Studio (SKB) Jln. Khatib Sultan No. 3 Kelurahan Kembang Kenanga Kec. Sail City of Pekanbaru. It aims to determine the performance of Pekanbaru City SKB employees. For the number of research informants, five informants consisted of core informants, control informants and observer informants.This study uses primary data taken at the Learning Activity Studio (SKB) Pekanbaru City. While the analysis used is descriptive qualitative which is processed using data reduction consisting of documentation, observation, and interviews. Qualitative data will be described by words or sentences separated by categories to obtain conclusions. From the analysis that the researchers did can be seen that the performance of employees in the Pekanbaru City Learning Center (SKB) is quite good, this is on all research variables namely knowledge about work, quality of work, productivity, adaptation, initiative and problem solving, cooperation, responsibility, and the ability to communicate and interact. Based on the specified assessment criteria, it can be concluded that the Employee Performance Analysis at the Learning Activities Studio (SKB) Jln. Khatib Sultan No. 3 Kelurahan Kembang Kenanga Kec. Sail Kota Pekanbar is quite good. The things that can be recommended in this research are organization management which only emphasizes the procedural approach but must be refined through changes in vision and mission, strategic approaches and operational activities in order to create excellent teamwork, working relationships based on participatory and group approaches teamwork in order to achieve the mission of an efficient organizationKey Words: Performance, Employee